The 5-Year Course of Neck Pain Among Natural Disaster Survivors: The Association of Prior Neck Pain with New Episodes of Neck Pain. Issue 4 (27th July 2021) - Yabe, Yutaka; Hagiwara, Yoshihiro; Sekiguchi, Takuya; Sugawara, Yumi; Tsuchiya, Masahiro; Yoshida, Shinichirou; Onoki, Takahiro; Takahashi, Tadahisa; Iwatsu, Jun; Tsuji, Ichiro
Abstract: Objective: Neck pain is a common health problem among both the general population and natural disaster survivors. However, the long-term course of neck pain has rarely been reported. The aim of this study was to elucidate the 5-year course of neck pain among survivors of the Great East Japan Earthquake (GEJE) by assessing the association of neck pain 2 and 4 years after the disaster with that at 7 years. Study design: Longitudinal study. Methods: A panel study was conducted on GEJE survivors (n = 1, 821) through the administration of a self-reported questionnaire at 2 (first time point), 4 (second time point), and 7 years (third time point) after the disaster. Multivariate logistic regression analyses were performed to assess the association between prior neck pain and subsequent neck pain. Results: The rates of neck pain at the first, second, and third time points were 20.7%, 21.1%, and 20.1%, respectively. Neck pain at the first time point was significantly associated with neck pain at the third time point (adjusted odds ratio [95% confidence interval]: 5.96 [4.53–7.83]). Furthermore, neck pain at the first and second time points was significantly associated with neck pain at the third time point (adjusted odds ratio [95% confidence interval]: 5.71 [4.19–7.78] for neck pain at either time point; 15.94 [10.99–23.12] for neck pain at both time points; P for trend <0.001). Conclusions: Prior neck pain was significantly associated with neck pain 5 years later, and the effect was stronger with an increase of prior neck pain episodes. Clinicians should base their selection of treatment method on an individual's history of neck pain.